Utility of Ultrasonography and Significance of Surgical Anatomy in the Management of de Quervain Disease: A Systematic Review and Meta-Analysis. Issue 2 (25th January 2022) - Abi-Rafeh, Jad; Mojtahed Jaberi, Mehrad; Kazan, Roy; Alabdulkarim, Abdulaziz; Boily, Mathieu; Thibaudeau, Stephanie
Abstract : Background: The role of ultrasound in plastic surgery practice has grown significantly over the past decade, with notable applications for conditions of the upper extremity. Its utility for the management of de Quervain disease, however, remains to be established, and the prevalence of first dorsal compartment anatomical variations needs to be adequately assessed. Methods: A systematic review was performed to evaluate the role of ultrasound in the diagnosis, anatomical characterization, and clinical management of de Quervain disease. A meta-analysis was conducted to establish the prevalence of first dorsal compartment anatomical variations in the de Quervain disease and general population, along with the diagnostic accuracy of ultrasound for their detection. Outcomes were documented and compared to alternative treatment options. Results: Extensor retinaculum thickening, tendon sheath swelling, peritendinous edema, and tendon enlargement were the most common sonographic features of de Quervain disease. The prevalence of an intercompartmental septum in the de Quervain disease surgical population was shown to be significantly greater than in the general cadaveric population (67 percent versus 35 percent, respectively). Although the efficacy of energy-based therapeutic ultrasound remains elusive, ultrasound-guided corticosteroid injections were shown to be more accurate than manual injections (90 to 100 percent versus 40 to 100 percent), and to confer significantly better treatment outcomes (73 to 100 percent versus 59 to 83 percent success rates, respectively). Conclusions: Ultrasound use is essential to achieve the best evidence-based outcomes in the management of de Quervain disease. The varied prevalence of first dorsal compartment anatomical variations and high accuracy of ultrasound for their detection carry significant prognostic implications.